Education of the gifted - Sharma, Sunita (Delhi : Shipra Publications, 2006)
The group of gifted children is marginalized in Indian educational system and there is a huge wastage of their potential. These children do not get desirable attention in any sphere of life including education. The reason behind this is their advanced intellectual capacity for which they have to suffer by way of receiving unsuitable education. Most of the parents also do not know anything about giftedness. When they are told that their child is a gifted one, they don't understand what it means and what they should do.
1. Intelligence -- 2. Giftedness -- 3. Characteristics of the gifted -- 4. Identification -- 5. Educating the gifted -- 6. Indian scenario.
Includes bibliographical references and index.
Keywords: SPECIAL EDUCATION